2017
DOI: 10.1007/s00404-017-4461-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there any relationship between adipocytokines and angiogenesis factors to address endothelial dysfunction and platelet aggregation in untreated patients with preeclampsia?

Abstract: Increase in the levels of antiangiogenic factors and leptin herewith decline in the level of other angiogenic factor PlGF, did not affect nitric oxide and platelet aggregation markers significantly. Increased levels of vWF and endoglin might be result of endothelial dysfunction, so our findings suggest that an impaired angiogenesis may address endothelial dysfunction, but not platelet aggregation for preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
12
0
2
Order By: Relevance
“…For example, leptin levels were found raised in the GD group of pregnant women, even when adjusting for confounders [86]. Higher serum leptin levels in pregnant women with PE have also been documented [91,92], and there is an association between higher leptin expression and intrauterine growth restriction (IUGR) [93,94]. To date, a few studies have shown a relationship between BPA and leptin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, leptin levels were found raised in the GD group of pregnant women, even when adjusting for confounders [86]. Higher serum leptin levels in pregnant women with PE have also been documented [91,92], and there is an association between higher leptin expression and intrauterine growth restriction (IUGR) [93,94]. To date, a few studies have shown a relationship between BPA and leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies illustrated the potential role of cytokines, chemokines, and their receptors in the development and progression of PE ( 19 , 20 , 21 ) . Pregnancy complications associated with PE are major causes of materno-fetal morbidity and mortality, but their pathogenesis remains unclear ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is produced by cytotrophoblasts and syncytiotrophoblasts in the human placenta and adipose tissue, which is then secreted into the circulation, where it exerts its effects via interaction with the LEPR. The effect of leptin on endothelial cells has attracted particular attention ( 20 , 26 ) . LEPRs are expressed in many normal tissues, but also in pathologic tissues generally associated with obesity and abnormal energy balance ( 27 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Its level increases in plasma as a result of endothelial damage. vWF increases platelet adhesion to subendothelial layer and contributes to thrombus formation [40,41].…”
Section: Endothelial Dysfunction and Cardiovascular Diseasesmentioning
confidence: 99%